Laser-based techniques for the non-invasive characterisation of grisaille paints on stained-glass windows - Carla Machado; Mohamed Oujja; Luís Cerqueira Alves; Marina Martínez-Weinbaum; Laura Maestro-Guijarro; Paula María Carmona-Quiroga; Marta Castillejo; Márcia Vilarigues; Teresa Palomar (Heritage Science, 2023)
Abstract Grisaille was the first paint applied on stained-glass panels, used in Europe since the twelfth century. Historical written sources described the use of iron and copper together with a high lead-silica base glass in the grisailles production. This project aims to study the evolution of the grisaille paint composition throughout time and the changes in the raw materials used in their production using non-destructive and non-invasive techniques. To achieve this objective, 23 grisaille samples dated from the 13th to the twentieth centuries from nine different countries (Portugal, Poland, United Kingdom, Sweden, Norway, Belgium, Low Countries, Germany, and France) were studied by means of micro particle-induced X-ray emission (μ-PIXE), micro energy dispersive X-ray fluorescence (μ-EDXRF), laser-induced breakdown spectroscopy (LIBS), laser-induced fluorescence (LIF), non-linear optical microscopy (NLOM) in the modality of multiphoton excitation fluorescence (MPEF) and optical microscopy (OM). The results showed that it was possible to identify compositional differences and patterns throughout the samples when compared with literature results. The preference for using copper in central and south-central European countries and the addition of new compounds (CoO, Cr2O3, MnO) as colouring agents since the nineteenth century was verified. The LIBS analyses allow the identification of boron on two samples, confirming the change of base glass components since the seventeenth century. The NLOM-MPEF showed the capability of this technique to measure the grisaille paint layers’ thickness. This non-invasive multi-analytical and complementary approach proves itself efficient in identifying changes in the grisaille’s composition throughout time, which can be interpreted as changes in the raw materials and manufacture used in the production of these paint materials.